Effect of leaching solutions on chemical durability of a natural metamict titanite. Issue 7 (2nd July 2020) - Sun, Yaping; Wang, Honglong; Zhang, Ming; Zhao, Wangxiong
ABSTRACT: Titanite (CaTiSiO5 ) a mineral that has shown promise as an actinide-bearing host phase. Natural titanites contain radionuclides which result in radiation damage to the crystal structure and could even lead to an amorphous state (metamict state). It is imperative to understand how the chemical durability of the titanites would be affected by such radiation damage and leaching solutions. Natural metamict titanite 2974 was studied by static leach tests at 200°C in different solutions, including heavy water (D2 O) and heavy-oxygen water (H2 18 O). The effects of these solutions on the leaching behaviour of the natural titanite with metamict structures were characterised using scanning electron microscopy (SEM), infrared spectrum (IR), Raman and X-ray diffraction (XRD), and the normalized leaching rates of the elements in the titanite were analysed using inductively coupled plasma mass spectrometry (ICP-MS) and optical emission spectroscopy (ICP-OES). The results indicate that in a pH 1 solution as well as a pH 11 solution, the leaching rates are comparatively low, even at a high temperature of 200°C. SiO2 and TiO2 were detected on the surface of the leached 2974, which indicates that the hydrothermal alteration abides to a mechanism of dissolution and re-precipitation. However, 2974 is mostly dissolved in a strongly acidic condition.